Drivers of teleworker productivity: A systematic review of the empirical evidence - Tapasco-Alzate, Omar; Giraldo-García, Jaime; Corpas-Iguarán, Eduardo; Garcés-Gómez, Yeison Alberto (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
This paper aims to identify the factors influencing teleworker productivity by reviewing empirical evidence found in the scientific literature on the topic. A systematic review was conducted to gather and evaluate primary literature sources, complemented by a bibliometric analysis of the volume, distribution, and trends in scientific production over the past 24 years. The effects found are heterogeneous, narrow in scope, and sometimes contradictory. Telework significantly impacts productivity, with its effects varying based on intensity, the nature of the tasks performed, and individual, social, and situational factors. This manuscript provides a comprehensive review of the factors influencing teleworker productivity, analyzing 318 research articles to identify the key determinants of productivity in remote work environments. It systematically categorizes these factors into individual, social, and situational dimensions, offering valuable insights for organizations and individuals adapting to the evolving landscape of telework.